2014
DOI: 10.1152/ajpgi.00038.2014
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus reuteri DSM 17938 differentially modulates effector memory T cells and Foxp3+ regulatory T cells in a mouse model of necrotizing enterocolitis

Abstract: Liu Y, Tran DQ, Fatheree NY, Rhoads JM. Lactobacillus reuteri DSM 17938 differentially modulates effector memory T cells and Foxp3 ϩ regulatory T cells in a mouse model of necrotizing enterocolitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 64 publications
3
81
1
Order By: Relevance
“…31 The potential mechanisms by which probiotics may prevent NEC have been extensively studied in experimental animal models. 86,[104][105][106][107][108][109][110][111][112][113][114][115][116] Specifically, their effect on TJs has been studied by a number of laboratories. In 2009, Khailova, at al., published that oral administration of Bifidobacterium bifidum (Bb) decreased elevated protein levels of ileal occludin and claudin-3 observed in neonatal rats with NEC.…”
Section: Development Of the Intestinal Epithelial Barriermentioning
confidence: 99%
“…31 The potential mechanisms by which probiotics may prevent NEC have been extensively studied in experimental animal models. 86,[104][105][106][107][108][109][110][111][112][113][114][115][116] Specifically, their effect on TJs has been studied by a number of laboratories. In 2009, Khailova, at al., published that oral administration of Bifidobacterium bifidum (Bb) decreased elevated protein levels of ileal occludin and claudin-3 observed in neonatal rats with NEC.…”
Section: Development Of the Intestinal Epithelial Barriermentioning
confidence: 99%
“…We studied an experimental NEC model and demonstrated that adoptive transfer of Tregs attenuated the severity of NEC, suggesting a role in controlling excessive inflammation . Our studies subsequently showed that oral administration of the probiotic L. reuteri DSM 17938 significantly increased the percentage of gut‐derived CD103 + DCs and Foxp3 + Tregs while diminishing the percentage of inflammatory T‐effector cells (including T H 1, T H 2 and T H 17) in the intestinal mucosa of newborn mice during NEC …”
Section: Preclinical Trials and Mechanism Of Action In Inflammatory Dmentioning
confidence: 79%
“…For example, as mentioned above, studies in the lab of Versalovic showed that L. reuteri strain ATCC PTA 6475 produces vitamin B 12 and histamine; the probiotic reduced tumor necrosis factor-α production via a protein kinase Adependent mechanism. 111 Subsequently, in our lab, a different strain of L. reuteri DSM 17938, which does not produce vitamin B 12 or increase histamine levels, did not reduce gut inflammation in rat intestine ex vivo, but prevented NEC 87 and markedly attenuated multiorgan inflammation in the scurfy mouse. 92 The mechanism involved, in contrast, was the activation of an adenosine A 2A receptor.…”
Section: Myths and Mysteriesmentioning
confidence: 84%
See 1 more Smart Citation
“…In a model of necrotizing enterocolitis, a Lactobacillus reuteri strain was found to restore the number of FOXP3 + Tregs. The majority of the Tregs were Helios + , possibly indicating thymic origin …”
Section: Introductionmentioning
confidence: 99%